Learning Strategies for SD Muhammadiyah 2 Waru During the Covid-19 Pandemic - Elfin Nur Diniyah; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This research was conducted to find out changes in the education sector caused by one of the viruses that is quite prevalent today, namely the corona virus which is widely known by the public as Covid-19. By using the method of data collection and interviews. The educational process that initially used face-to-face activities carried out in schools has now become online that can be done at home, where students and teachers use online methods through various fairly sophisticated applications. Advances in information technology are very supportive in the learning process during the Covid-19 pandemic. This makes it easier for students to access various materials presented by the teacher. The purpose of the study was to determine the learning strategies used at SD Muhammadiyah 2 Waru during the Covid-19 pandemic. And naming the character of students in accordance with the Muhammadiyah curriculum and pioneering the progress and development of education, as well as various parties in improving the quality of education at SD Muhammadiyah 2 Waru. The results of the study show that the strategy used by SD Muhammadiyah 2 Waru at this time is to use online learning methods which are carried out online and offline learning which is carried out face-to-face in accordance with school rules and regulations and apply fairly strict health protocols. Based on the research that has been done, it can be concluded that the Covid-19 pandemic has had a considerable impact on the world of education. As well as advances in information technology that has been very advanced connecting students and teachers in using various applications such as whatsapp groups, google class and zoom. Apart from that, many people are paying attention to the current prokes.